SISTEM INFORMASI PERSEDIAAN BAHAN BAKU BERBASIS WEBSITE (STUDI KASUS: WARUNG SOP AYAM PAK MIIN RC VETERAN BINTARO) - Sabilla Nugroho (2023)
Technology has become a very important tool in human life, including in the business world such as Warung Sop Ayam Pak Miin. Even so, at Pak Miin's Chicken Soup Shop, the use of technology has not been fully utilized, especially in the raw material inventory data collection system which is still done manually using records in books. This method takes a long time in the work process and often causes data discrepancies between the center and branches. In addition, the use of manual systems also has high risks, such as data loss, data duplication, and data corruption. Therefore, the author designs a raw material inventory information system that aims to facilitate the handling and data collection of raw materials and reduce the risks that may occur at Pak Miin's Chicken Soup Stall. The author uses the waterfall system design method, Unified Modeling Language (UML) visual modeling, and conducts PIECES problem analysis. This system was developed using the PHP programming language and MySQL database. The result of this research is a website that is able to help the process of handling and recording raw materials in real-time and always updated.